Research progress on the role of FGF21 in insulin resistance - Zhang, Haixin; Zhu, Rongyu; Sun, Quanhao; Du, Likun (Frontiers in Endocrinology, 2025)
The elevated global prevalence of metabolic syndrome and type 2 diabetes mellitus (T2DM) has led to a dramatic increase in patients with insulin resistance. The majority of insulin resistance is closely associated with obesity and metabolic syndrome, resulting in impaired insulin signaling pathways. type 2 diabetes can be preceded by insulin resistance, and therefore, it is crucial to stop the progression of insulin resistance to type 2 diabetes. Fibroblast growth factor 21 (FGF21) holds a bright future in the therapeutic study of insulin resistance; it is involved in the regulation of lipid metabolism and immune homeostasis while ameliorating the impaired insulin signaling pathway, improving the state of insulin resistance through multiple aspects. In this review, we describe the physiological properties and signaling pathways of FGF21 and elaborate on the mechanism of action of FGF21 in improving insulin resistance. Finally, the progress of FGF21 analog research is summarized in the context of the treatment of insulin resistance.